2019
DOI: 10.1038/s41598-019-56031-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel cholesterol-lowering dipeptide, phenylalanine-proline (FP), and its down-regulation of intestinal ABCA1 in hypercholesterolemic rats and Caco-2 cells

Abstract: There has been no report about in vivo active cholesterol-lowering dipeptide in any protein origin, despite their potential health benefits. Cattle heart protein hydrolysate ultra-filtrate (HPHU, molecular weight < ca. 1,000 Da peptide mixture) exhibits cholesterol-lowering activity in hypercholesterolemic rats, but the active peptide in HPHU that lowers serum cholesterol levels and its molecular mechanism are unknown. In this study, we separated and purified HPHU to identify a novel cholesterol-lowering dipep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Interestingly, a recent study in mice reported that intestinal ABCA1 knockout reduced cholesterol absorption by ≈28% and total plasma cholesterol by approximately 30% [ 22 ]. Our previous study revealed that the suppression of intestinal cholesterol absorption by a novel cholesterol-lowering dipeptide, phenylalanine-proline (FP), was associated with a reduction in intestinal ABCA1 expression levels [ 12 ]. These results suggest that the inhibitory effect IIAEK exerts on cholesterol absorption is likely to be accompanied by a decrease in the expression of ABCA1 in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, a recent study in mice reported that intestinal ABCA1 knockout reduced cholesterol absorption by ≈28% and total plasma cholesterol by approximately 30% [ 22 ]. Our previous study revealed that the suppression of intestinal cholesterol absorption by a novel cholesterol-lowering dipeptide, phenylalanine-proline (FP), was associated with a reduction in intestinal ABCA1 expression levels [ 12 ]. These results suggest that the inhibitory effect IIAEK exerts on cholesterol absorption is likely to be accompanied by a decrease in the expression of ABCA1 in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caco-2 cells were grown in 6-well Transwell ® plates (Corning, Inc., Corning, NY, USA) containing 0.5 mL DMEM supplemented with fetal bovine serum for 14 days post-confluence. The absorption of [ 14 C]-labeled micellar cholesterol in Caco-2 cells was measured as previously described [ 12 , 13 ], with some modifications. Briefly, on day 14, [ 14 C]-labeled micellar solutions containing 3.7 kBq [4- 14 C]-cholesterol (2.0 Gbq/mmol, NEN) with or without 2 mM IIAEK, 5 mM taurocholate, and 250 μM cholesterol in serum-free DMEM were prepared by sonication and incubated with shaking at 37 °C for 24 h. Following incubation, cholesterol absorption was measured for 24 h. The cellular protein concentration was determined using a commercially available kit (Bio-Rad Protein Assay; Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations